THE IMPACT OF SUPPLY CHAIN AND SUPPLIER EVALUATION RELATED PRACTICES ON THE PERFORMANCE OF AUTOMOTIVE INDUSTRY IN THAILAND - Somjai, Sudawan; Chandarasorn, Voradej; Vasuvanich, Saroge (International Journal of Supply Chain Management, 2019)
This study explores the practices of supply chain and evaluation practices of supplier concerning the firm performance of automotive industry of Thailand. Data were collected from the managers of the supply chain and the production managers through a questionnaire. PLS-SEM is used to explore the association among the understudy variables. The results revealed that effective practices of the supply chain could increase the performance of the industry in the country. Similarly, effective practices of supplier evaluation also can increase the performance of the firm. This study suggested to the policymakers and the manager of the supply chain that they must apply only an effective SCM and supplier evaluation practices in the firm. These effective practices can only have the ability to enhance the performance of every process of the firm.